Burned-out Metastatic Yolk Sac Tumour: A Rare Case Report - Jyoti Mishra; Monal Trisal; Anshu Gupta (Dr. Annil Mahajan, 2024)
Burned-out testicular tumor is a very rare clinical entity. There are no clinical findings in the testicle because it regresses spontaneously without any treatment and generally presents with metastases. Burnt out testicle is often seen with Yolk sac tumour. The diagnosis of yolk sac tumours is usually a multimodality diagnosis including a biopsy of the lesion. We describe a case of metastatic yolk sac tumours that presented with deposits in inguinal lymph nodes. No testicular tumour was identified in our case.